2008
DOI: 10.1002/pits.20319
|View full text |Cite
|
Sign up to set email alerts
|

A survey investigating school psychologists' measurement of treatment integrity in school‐based interventions and their beliefs about its importance

Abstract: A survey of individuals holding the Nationally Certified School Psychologist (NCSP) credential was conducted via the Internet to gather information regarding their measurement of treatment integrity in school‐based interventions and their beliefs about its importance. A sample of 806 self‐selected professionals holding the NCSP credential provided data about the extent to which they measure treatment integrity and the methods they used to measure it when developing interventions via one‐to‐one and group/team c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 6 publications
7
74
1
Order By: Relevance
“…This yielded a response rate of approximately 10%, which was similar to that of other online surveys of NASP members (for example, see Cochrane & Laux, 2008). It is not known how the exclusion of trainers, students, and private practitioners affected the size of the target sample, but one recent report on NASP membership indicated that of 21,997 paid members, 10,906 (49.58%) reported employment in school settings (Infocus, 2007).…”
Section: Participantsmentioning
confidence: 60%
See 1 more Smart Citation
“…This yielded a response rate of approximately 10%, which was similar to that of other online surveys of NASP members (for example, see Cochrane & Laux, 2008). It is not known how the exclusion of trainers, students, and private practitioners affected the size of the target sample, but one recent report on NASP membership indicated that of 21,997 paid members, 10,906 (49.58%) reported employment in school settings (Infocus, 2007).…”
Section: Participantsmentioning
confidence: 60%
“…The study was also limited by its reliance on current members of NASP, who may differ from nonmembers; however, recent research suggests that NASP samples are generally representative of school psychologists as a population (Lewis, Truscott, & Volker, 2008). The web-based procedures used for their efficiency and cost-effectiveness yielded a response rate that is low by some standards (Cook, Heath, & Thompson, 2000), but not unusual for online survey research (e.g., Cochrane & Laux, 2008). As such, the sample may not be representative of practicing school psychologists.…”
Section: Limitationsmentioning
confidence: 98%
“…Our practitioners felt that school staff lacked an awareness and understanding of the purpose of intervention integrity, and school staff reported feeling that Heartland was evaluating them. In a recent survey, school psychologists also reported this perceived lack of communication (Cochrane & Laux, 2008). As such, research is needed on how best to integrate integrity monitoring within existing school services without being perceived as evaluative.…”
Section: Lessons Learnedmentioning
confidence: 89%
“…A recent survey of 806 self-selected Nationally Certified School Psychologists (NCSP) was conducted to ascertain whether they measure intervention integrity in school-based interventions as well as their beliefs about its importance School Mental Health (2009) 1:143-153 145 (Cochrane & Laux, 2008). Only 11.3% of the participants reported measuring intervention integrity during the development, monitoring, and evaluation of interventions.…”
Section: School-based Intervention Literaturementioning
confidence: 99%
See 1 more Smart Citation